Insulin-like peptide 3 (INSL3) as an indicator of leydig cell insufficiency (LCI) in Middle-aged and older men with hypogonadism: reference range and threshold - Ravinder Anand-Ivell; Kee Heng; Leen Antonio; Gyorgy Bartfai; Felipe F. Casanueva; Mario Maggi; Terence W. O’Neill; Margus Punab; Giulia Rastrelli; Jolanta Slowikowska-Hilczer; Jos Tournoy; Dirk Vanderschueren; et al. (The Aging Male)
Insulin-like peptide 3 (INSL3) is a circulating biomarker for Leydig cell functional capacity in men, also indicating Leydig Cell Insufficiency (LCI) and potential primary hypogonadism. Using results from large cohort studies we explore sources of biological and technical variance, and establish a reference range for adult men. It is constitutively secreted with little within-individual variation and reflects testicular capacity to produce testosterone. The main INSL3 assays available indicate good concordance with low technical variance; there is no effect of ethnicity. INSL3 declines with age from 35 years at about 15% per decade. Like low calculated free testosterone, and to a lesser extent low total testosterone, reduced INSL3 is significantly associated with increasing age-related morbidity, including lower overall sexual function, reflecting LCI. Consequently, low INSL3 (≤0.4 ng/ml; ca. <2 SD from the population mean) might serve as an additional biochemical marker in the assessment of functional hypogonadism (late-onset hypogonadism, LOH) where testosterone is in the borderline low range. Excluding individuals with low LCI (INSL3 ≤ 0.4 ng/ml) leads to an age-independent (> 35 years) reference range (serum) for INSL3 in the eugonadal population of 0.4 − 2.3 ng/ml, with low INSL3 prospectively identifying individuals at risk of increased future morbidity.